Goldenrod : poems - Smith, Maggie, 1977- (One Signal Publishers/Atria, 2021)
"With her breakout bestseller Keep Moving, Maggie Smith captured the nation with her "meditations on kindness and hope" (NPR). Now, with Goldenrod, the award-winning poet returns with a powerful collection of poems that look at parenthood, solitude, love, and memory. Pulling objects from everyday life--a hallway mirror, a rock found in her son's pocket, a field of goldenrods at the side of the road--she reveals the magic of the present moment. Only Maggie Smith could turn an autocorrect mistake into a line of poetry, musing that her phone "doesn't observe / the high holidays, autocorrecting / shana tova to shaman tobacco, / Rosh Hashanah to rose has hands" -- Amazon.